Orofacial Pain with Cardiac Origin of Coronary Artery Disease: A Case Report and Literature Review - Eunhye Choi; Yeon-Hee Lee; Hee-Kyung Park (Hindawi Limited, 2023)
When diagnosing orofacial pain, clinicians should also consider non-odontogenic origin and systemic diseases as possible etiological factors, along with odontogenic origin. This case report aimed to provide information for early detection of orofacial pain of cardiac origin by dentists, when pain due to coronary artery disease is the only presenting symptom. A 60-year-old male patient with unexplained isolated bilateral jaw pain that had persisted for the past 5 years was referred to a dentist by an anesthesiologist who suspected temporomandibular joint disorder. In oral examination, no specific pathological changes were observed in the oral cavity, including teeth, surrounding alveolar bone, and buccal mucosa. Magnetic resonance imaging and conventional radiography showed no pathological destruction or abnormalities of bone and soft tissue in the temporomandibular joint region. However, pain was precipitated by ordinary daily activities, and the pain alleviating factor was rest. Eventually, the patient was referred to a cardiologist for further evaluation since his pain was induced by physical activity. Coronary artery disease (CAD) was diagnosed using coronary computed tomography angiography, and the pain was considered to be angina pectoris. Percutaneous coronary intervention was successfully done for the patient, after which his orofacial symptoms disappeared. To conclude, isolated craniofacial pain of cardiac origin may lead to patients seeking dental care or visiting orofacial pain clinics. In these settings, dentists and orofacial pain specialists may contribute to the diagnosis of CAD and refer patients for cardiac evaluation and appropriate management.